(untitled) (Journal of Computational Mathematics, 2000)
Let P be a transition matrix of a Markov chain and be of the form P=( matrix P_11 &P_12 P_21 &P_22 matrix ). The stationary distribution π^T is partitioned conformally in the form (π^T_1, π^T_2). This paper establish the relative error bound in π^T_i (i=1,2) when each block P_ij get a small relative perturbation.